Fish Diversity and Spatial Patterns in the Upper Yangtze River National Nature Reserve for Rare and Endemic Fish Based on Environmental DNA (eDNA) Technology - Xiaohan Dong; Jiaxin Huang; Zongqiang Qi; Ziwei Wang; Qing Zuo; Yanjun Shen (Fishes, 2025)
The Upper Yangtze River National Nature Reserve for Rare and Endemic Fish is a critical sanctuary facing increasing pressure from hydropower development. To assess its current ecological state, we employed environmental DNA (eDNA) metabarcoding on 48 water samples collected from 16 transects in August 2024. Our analysis identified 93 fish species from 3 orders, 13 families, and 67 genera, of which 89 were consistent with historical records. The Cyprinidae family was dominant. The fish community was predominantly characterized by slow-flowing, benthic, omnivorous, and migratory taxa that lay adhesive eggs, with key life-history traits including a sexual maturity age of 1–4 years and a length at first maturity under 20 cm. Spatially, species richness was highest in the Chishui River (64 species), followed by the Minjiang River (61 species). While alpha diversity was largely consistent across most rivers (except the Minjiang), beta diversity analysis revealed significant compositional differences among basins (PERMANOVA, R2 = 0.2747, p = 0.001). Notably, the Chishui River supported not only the highest richness but also a distinct community structure. In summary, this study provides a systematic current status assessment of the reserve’s fish resources, revealing significant spatial heterogeneity, Our findings underscore the potential impacts of dam construction and offer a scientific basis for informing effective conservation strategies.